The Effect of the Integration of Spaced Repetition and Quizlet on English Speaking Skills at the Elementary School Level - Renata Dwi Iswanti; Indah Nurmahanani; Nadia Tiara Antik Sari (Al-Madrasah: Jurnal Ilmiah Pendidikan Madrasah Ibtidaiyah, 2026)
This study aims to investigate the influence of the Spaced Repetition (SR) method assisted by Quizlet media on the improvement of English speaking skills of elementary school students. The research design used a quasi-experiment with Nonequivalent Control Group Design. The sample consisted of two groups: the experimental group that was taught with the integration of SR and Quizlet, and the control group that was taught by the Direct Instruction/Shadowing method. Students' initial abilities are measured through the pretest, and the final achievement through the same posttest. The results of the descriptive analysis showed a more significant increase in the experimental group. The mean increased from 62.96 to 84.07 (a difference of 21.11 points), while the control group only increased from 58.34 to 72.41 (difference of 14.07 points). A decrease in standard deviation in the experimental group (9,935 to 9,043) indicated a better equitable distribution of abilities. The results of the inferential statistical test reinforce these findings. The Independent Sample T-Test on the posttest data yielded a significance value of p = 0.001 (p < 0.01), which proves a statistically significant difference in improvement between the two groups. Simple linear regression analysis revealed that the SR-Quizlet method was a strong predictor of ability improvement, with a contribution of 64.7% (Coefficient of Determination R² = 0.647). It was concluded that the integration of the Spaced Repetition method and Quizlet media was effective and superior in improving the English speaking skills of elementary school students compared to conventional methods. This success is supported by a synergistic three-phase learning syntax: (1) reinforcement of early memory through a multisensory approach, (2) consolidation of long-term memory through gamified Spaced Repetition and Active Recall, and (3) improvement of productive skills through contextual application. This study recommends this model as an innovative, evidence-based strategy for teaching speaking at the elementary level.